A sensitive indirect competitive enzyme-linked immunosorbent assay for the detection of sarsasapogenin in rat plasma - Wang Jing; Liu Ji-hua; Guo Xu; Zhang Jian; Yu Bo-yang (Acta Pharmacologica Sinica, 2016)
Aim: To generate a polyclonal antibody against sarsasapogenin and to develop an indirect competitive enzyme-linked immunosorbent assay (IC-ELISA) method for the pharmacokinetic study of Sarsasapogenin in rats. Methods: The antigen of sarsasapogenin was produced using an active ester method and subsequently used for raising polyclonal antibodies in rabbits. The specificity and sensitivity of the antibody were measured by IC-ELISA. Using the ELISA method, sarsasapogenin levels were measured in the serum of rats after an oral dose of 100 mg/kg. Results: Polyclonal antibodies raised against sarsasapogenin-bovine serum albumin were generated and showed a high reactivity to sarsasapogenin. The antibodies exhibited minor cross-reactivity to ruscogenin (23%), diosgenin (22%), 25 (R, S) ruscogenin l-O-[β-D-glucopyranosyl (1→2)][β-D-xylopyranosyl (1→3)]-β-D-fucopyranoside (26%) and no cross-reactivity to diammonium glycyrrhizinate and notoginseng R1. The detection range of sarsasapogenin by this ELISA method was approximately 2.4−760 ng/mL. The recovery rates of 10 ng/mL, 100 ng/mL, and 500 ng/mL were in the range of 91.0%−96.2% for intra-assay and 89.0%–92.0% for inter-assay. The coefficients of variation (CV%) for intra- and inter-assays at the three different sarsasapogenin levels were 3.1%–8.3% (n=6) and 6.0%-14.1% (n=6), respectively. Conclusion: The IC-ELISA method is a sensitive test for the determination of sarsasapogenin concentration in rat plasma and for pharmacokinetic (PK) studies.